Comparing cytocompatibility of two fluoride-containing solutions and two resin-based restorative materials—a pilot study - Mulder, Riaan; Noordien, Naeemah; Potgieter, Nicoline (Frontiers in Oral Health, 2024)
Background Cytocompatibility should always be considered, especially if the surface of treated carious lesions is close to soft tissue or is accidentally exposed to the oral soft tissue by the clinician. Methods The aim of the present study was to compare the cytocompatibility of two fluoride-containing liquids and two resin-containing restorative materials with buccal mucosa fibroblasts. The fluoride-containing materials were silver diamine fluoride and water-based silver fluoride. Results The statistical analysis was completed by comparing the positive control growth of the buccal mucosa fibroblasts to the growth of cells exposed to various materials. The one-way ANOVA with Tukey’s HSD result was completed. All the assessed materials compared to the control wells for both the 24 and 48 h time intervals indicated a significant cytocompatibility result, except for the test wells with Stela (SDI) at the 24 h time interval. There was no significant difference between the step 2 liquids and the two dental materials in cytocompatibility at the 24 h interval. All four materials indicated no significant differences between the cytocompatibility of any dental materials for 48 h. Conclusion The cytocompatibility assessment for Riva Star and Riva Star Aqua with the direct method in a full dispensing drop is not viable for step 1 of the fluoride-containing liquids. The use of Stela Light Cure is a suitable material that will be in contact with buccal mucosa as it showed potential for increased cytocompatibility compared to Riva Light Cure. Riva Star Aqua is more cytocompatible than Riva Star.